Preparation method of PPS diaphragm capable of increasing breaking strength of PPS diaphragm
By using polyphenylene sulfide, polyethersulfone and lignin in the PPS diaphragm, and combining the surface modification and crosslinking structure of carbon fibers, the problem of low fracture strength of existing PPS diaphragm fibers is solved, and high fracture strength is achieved and corrosion resistance, simplifies the process and reduces costs.
Patent Information
- Application Number
- CN202411280212.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-20
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
After hydrophilic modification treatment, the fiber breaking strength of the existing PPS diaphragm decreases, affecting the strength and service life of the diaphragm, and the process is complicated and the cost is high.
Compound PPS fibers are prepared by polyphenylene sulfide, polyether sulfone and lignin, and modified carbon fibers are coated with organic matter, and cross-linked structures are formed by combining beating, dispersing, hot pressing and other processes to improve the fracture strength of the PPS diaphragm.
It significantly improves the fracture strength, corrosion resistance and oxidation resistance of the PPS diaphragm, simplifies the process, reduces costs, and is suitable for large-scale industrial production.
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer materials and engineering technology, and particularly relates to a method for preparing a PPS diaphragm capable of increasing the fracture strength of the PPS diaphragm. Background Art
[0002] Diaphragms play an important role in the production of hydrogen by alkaline water electrolysis. Commonly used are asbestos diaphragms and polyphenylene sulfide woven diaphragms. At present, the diaphragms for the production of hydrogen by alkaline water electrolysis in China mainly use polyphenylene sulfide woven diaphragms; polyphenylene sulfide (PPS) is a crystalline thermoplastic polymer. In the diaphragm with polyphenylene sulfide (PPS) fabric as the base, polyphenylene sulfide (PPS) fabric as the base can provide a certain physical support effect. It has good heat resistance and excellent corrosion resistance, and is widely used in industrial filter materials. At the same time, PPS fabric has the characteristics of excellent heat resistance, high mechanical strength and excellent electrical properties. However, the hydrophilicity of polyphenylene sulfide diaphragms is poor, resulting in a large surface resistance of the diaphragm and a large power loss. Therefore, the existing PPS fibers are subjected to a post-hydrophilic modification treatment. This method has a long process and high cost. The fiber breaking strength is reduced after modification, which has a great impact on the strength of the membrane, thereby affecting the service life. Summary of the invention
[0003] The invention discloses a method for preparing a PPS diaphragm with increased fracture strength, which comprises preparing composite PPS fibers from polyphenylene sulfide, polyethersulfone and lignin, surface modifying the carbon fibers and coating them with organic matter to form modified carbon fibers, then mixing the composite PPS fibers with the modified carbon fibers, pulping, debonding, papermaking and hot pressing to prepare a base film, and then forming a cross-linked structure on the base film to obtain a PPS diaphragm with high fracture strength.
[0004] Specifically, the present invention provides a method for preparing a PPS diaphragm for increasing the fracture strength of the PPS diaphragm, comprising:
[0005] 1) Mix polyphenylene sulfide, polyether sulfone, and lignin, heat to above 300°C for melt spinning, and cut to obtain PPS composite fiber;
[0006] 2) adding carbon fiber to hydrochloric acid, heating, filtering, washing, and drying to obtain activated carbon fiber; adding the activated carbon fiber to n-butanol, adding zirconium n-butoxide, adding acetic acid to adjust the Ph value, heating for acidification and hydrolysis, filtering the product, washing, and drying it, and then placing it in a heating furnace into which a mixed gas of ammonia and nitrogen is introduced, heating to 700-800° C. for insulation, cooling to room temperature, taking it out, and then adding it to an aqueous solution containing dopamine, and then adding trishydroxymethylaminomethane, adding hydrochloric acid to adjust the Ph value of the mixed solution, heating for in-situ polymerization and coating, filtering, washing, and drying to obtain modified carbon fiber;
[0007] 3) putting the composite fiber of step 1) and the modified carbon fiber of step 2) into deionized water for dispersion, pulping, debonding, papermaking, and hot pressing to obtain a PPS separator;
[0008] 4) dispersing polysulfone and tris(2-hydroxyethyl)isocyanurate in isopropanol to obtain an oily solution, and dispersing polyethyleneimine and polyvinylpyrrolidone in a mixed solvent of diethylene glycol and deionized water to obtain an aqueous solution;
[0009] 5) The PPS membrane obtained in step 3) is first immersed in an oily solution, maintained, taken out, dried, and then immersed in an aqueous solution, maintained, taken out, and dried. The above process is repeated multiple times to obtain the PPS membrane.
[0010] Furthermore, in step 1), 80-100 parts by mass of polyphenylene sulfide, 25-30 parts by mass of polyether sulfone, and 8-12 parts by mass of lignin are mixed, heated to 300-320°C for melt spinning, and cut to obtain PPS composite fibers; the number average molecular weight of the polyphenylene sulfide is 20,000-30,000; the number average molecular weight of the polyether sulfone is 40,000-50,000, and the number average molecular weight of the lignin is 1,000-1,200.
[0011] Further, in step 2), the carbon fiber is added to 0.8-1.2 mol / L hydrochloric acid and heated at 70-80° C. for 4-8 hours.
[0012] Filter, wash, and dry to obtain activated carbon fiber; add the activated carbon fiber to n-butanol, add zirconium n-butoxide, wherein the concentration of zirconium n-butoxide is 3-5wt%, add acetic acid to adjust the Ph value to 5.5-6.5, heat to 60-70°C, perform acid hydrolysis, filter the product, wash, and dry, then place it in a heating furnace and pass a mixed gas of ammonia and nitrogen, wherein the mixed gas contains 2-5 volume % ammonia and the balance is nitrogen, heat to 700-800°C for 3-5h, cool to room temperature, take out, and then add to an aqueous solution containing 15-20wt% dopamine, then add tris(hydroxymethyl)aminomethane) of the same mass as dopamine, add hydrochloric acid to adjust the Ph value of the mixed solution to 7-8, heat to 60-80°C and keep for 20-40min, filter, wash, and dry to obtain modified carbon fiber
[0013] Furthermore, in step 3), the mass ratio of the composite fiber to the modified carbon fiber is 10-15:1-2; the pulping concentration is 3-5wt%, the papermaking concentration is 0.5-0.8%, the hot pressing pressure is 15-20Mpa, and the hot pressing temperature is 200-240°C.
[0014] Furthermore, in step 4), 20-25 parts by mass of polysulfone and 15-20 parts by mass of tris(2-hydroxyethyl)isocyanurate are dispersed in 100 parts by mass of isopropanol to obtain an oily solution.
[0015] Further, in step 4), 8-12 parts by mass of polyethyleneimine and 5-8 parts by mass of polyvinylpyrrolidone are dispersed in a mixed solvent of 100 parts by mass of diethylene glycol and deionized water to obtain an aqueous solution, wherein the mass ratio of diethylene glycol to deionized water is 3:7-2:8
[0016] Furthermore, the PPS membrane obtained in step 3) is first immersed in an oily solution, kept for 5-10 minutes, taken out, dried, and then immersed in an aqueous solution, kept for 5-10 minutes, taken out, dried, and the above process is repeated 2-5 times to obtain the PPS membrane.
[0017] Furthermore, a PPS diaphragm with high breaking strength is provided, and the diaphragm is prepared by the preparation method.
[0018] Beneficial technical effects:
[0019] Compared with the prior art, the beneficial effects of the present invention are:
[0020] 1) Adding polyethersulfone and lignin to polyphenylene sulfide, lignin will be partially decomposed under the high temperature during melting, and the chemical bonds of the polyphenol structure will be broken to produce phenolic compounds. Under the action of phenolic compounds, polyethersulfone and polyphenylene sulfide can improve the crystallization properties of the composite, thereby improving the mechanical properties and corrosion resistance of the PPS composite fiber;
[0021] 2) The zirconium hydroxide nanoparticles are formed on the surface of the carbon nanofibers by acidic hydrolysis of zirconate, and then a coating structure of partial zirconium nitride and zirconium oxynitride is formed by heat treatment, and the carbon fiber is modified by nitrogen doping, thereby improving the mechanical properties of the carbon fiber. Part of the residual zirconium oxide can act as a catalyst during the in-situ polymerization of dopamine, so that polydopamine is evenly coated on the surface of the carbon fiber, thereby improving the coating effect of dopamine on the carbon fiber; polydopamine and composite PPS fiber have excellent affinity and adhesion, thereby improving the bonding effect between the carbon fiber and the PPS fiber, and improving the fracture strength of the PPS diaphragm;
[0022] 3) Polysulfone, tris (2-hydroxyethyl) isocyanurate, polyethyleneimine, and polyvinyl pyrrolidone are copolymerized to form a cross-linked structure, thereby increasing the bonding strength between the carbon fiber and PPS in the diaphragm and further increasing the fracture strength of the diaphragm;
[0023] 4) The diaphragm of the present invention has high corrosion resistance, high oxidation resistance, high fracture strength, simple operation, low cost, and is easy for large-scale industrial production. DETAILED DESCRIPTION
[0024] The present invention is further described below in conjunction with specific embodiments. However, the protection scope of the present invention is not limited to the following embodiments, and any non-essential adjustments and modifications made to the present invention based on the above invention content still fall within the protection scope of the present invention.
[0025] Example 1
[0026] 1) 80 parts by weight of polyphenylene sulfide, 25 parts by weight of polyether sulfone, and 8 parts by weight of lignin are mixed, heated to 300° C. for melt spinning, and cut to obtain PPS composite fibers; the number average molecular weight of the polyphenylene sulfide is 25,000; the number average molecular weight of the polyether sulfone is 45,000, and the number average molecular weight of the lignin is 1,200;
[0027] 2) adding carbon fiber to 0.8 mol / L hydrochloric acid, heating at 70° C. for 4 h, filtering, washing, and drying to obtain activated carbon fiber; adding the activated carbon fiber to n-butanol, adding zirconium n-butoxide, wherein the concentration of zirconium n-butoxide is 3 wt %, adding acetic acid to adjust the Ph value to 5.5, heating to 60° C., acidifying and hydrolyzing, filtering the product, washing,
[0028] After drying, the mixture is placed in a heating furnace and introduced with a mixture of ammonia and nitrogen, wherein the mixture contains 5% by volume of ammonia.
[0029] The balance is nitrogen, heated to 700°C for 3 hours, cooled to room temperature, taken out, and then added to an aqueous solution containing 15wt% dopamine, and then tris(hydroxymethylaminomethane) of the same mass as dopamine was added, and hydrochloric acid was added to adjust the Ph value of the mixed solution to 7, heated to 60°C for 20 minutes, filtered, washed, and dried to obtain modified carbon fibers;
[0030] 3) The composite fiber of step 1) and the modified carbon fiber of step 2) are put into deionized water at a mass ratio of 10:1 for dispersion, pulping, decomposition, papermaking, and hot pressing to obtain a PPS diaphragm; the pulping concentration is 4wt%, the papermaking concentration is 0.6%, the hot pressing pressure is 20Mpa, and the hot pressing temperature is 220°C;
[0031] 4) dispersing 20 parts by mass of polysulfone and 15 parts by mass of tris(2-hydroxyethyl)isocyanurate in 100 parts by mass of isopropanol to obtain an oily solution, dispersing 8 parts by mass of polyethyleneimine and 5 parts by mass of polyvinylpyrrolidone in 100 parts by mass of a mixed solvent of diethylene glycol and deionized water to obtain an aqueous solution, wherein the mass ratio of diethylene glycol to deionized water is 3:7;
[0032] 5) The PPS membrane obtained in step 3) is first immersed in an oily solution, kept for 5 minutes, taken out, dried, and then immersed in an aqueous solution, kept for 5 minutes, taken out, and dried. The above process is repeated 5 times to obtain the PPS membrane.
[0033] Example 2
[0034] 1) 100 parts by mass of polyphenylene sulfide, 30 parts by mass of polyether sulfone, and 12 parts by mass of lignin are mixed, heated to 320° C. for melt spinning, and cut to obtain PPS composite fibers; the number average molecular weight of the polyphenylene sulfide is 25,000; the number average molecular weight of the polyether sulfone is 45,000, and the number average molecular weight of the lignin is 1,200;
[0035] 2) adding carbon fiber to 1.2 mol / L hydrochloric acid, heating at 80°C for 8h, filtering, washing, and drying to obtain activated carbon fiber; adding the activated carbon fiber to n-butanol, adding zirconium n-butoxide, wherein the concentration of zirconium n-butoxide is 5wt%, adding acetic acid to adjust the Ph value to 6.5, heating to 70°C, acidifying and hydrolyzing, filtering the product, washing,
[0036] After drying, the mixture is placed in a heating furnace and introduced with a mixture of ammonia and nitrogen, wherein the mixture contains 2% ammonia by volume.
[0037] The balance is nitrogen, heated to 800°C for 5 hours, cooled to room temperature, taken out, and then added to an aqueous solution containing 20wt% dopamine, and then tris(hydroxymethylaminomethane) of the same mass as dopamine was added, and hydrochloric acid was added to adjust the Ph value of the mixed solution to 8, heated to 80°C for 40 minutes, filtered, washed, and dried to obtain modified carbon fibers;
[0038] 3) The composite fiber of step 1) and the modified carbon fiber of step 2) are put into deionized water at a mass ratio of 10:1 for dispersion, pulping, decomposition, papermaking, and hot pressing to obtain a PPS diaphragm; the pulping concentration is 4wt%, the papermaking concentration is 0.6%, the hot pressing pressure is 20Mpa, and the hot pressing temperature is 220°C;
[0039] 4) dispersing 25 parts by mass of polysulfone and 20 parts by mass of tris(2-hydroxyethyl)isocyanurate in 100 parts by mass of isopropanol to obtain an oily solution, dispersing 12 parts by mass of polyethyleneimine and 8 parts by mass of polyvinylpyrrolidone in a mixed solvent of 100 parts by mass of diethylene glycol and deionized water to obtain an aqueous solution, wherein the mass ratio of diethylene glycol to deionized water is 2:8;
[0040] 5) The PPS membrane obtained in step 3) is first immersed in an oily solution, kept for 10 minutes, taken out, dried, and then immersed in an aqueous solution, kept for 10 minutes, taken out, and dried. The above process is repeated twice to obtain the PPS membrane.
[0041] Example 3
[0042] 1) 90 parts by weight of polyphenylene sulfide, 28 parts by weight of polyether sulfone, and 10 parts by weight of lignin are mixed, heated to 310° C. for melt spinning, and cut to obtain PPS composite fibers; the number average molecular weight of the polyphenylene sulfide is 25,000; the number average molecular weight of the polyether sulfone is 45,000, and the number average molecular weight of the lignin is 1,200;
[0043] 2) adding carbon fiber to 1.0 mol / L hydrochloric acid, heating at 75° C. for 6 h, filtering, washing, and drying to obtain activated carbon fiber; adding the activated carbon fiber to n-butanol, adding zirconium n-butoxide, wherein the concentration of zirconium n-butoxide is 4 wt %, adding acetic acid to adjust the Ph value to 6.0, heating to 65° C., acidifying and hydrolyzing, filtering the product, washing,
[0044] Dry, then place in a heating furnace and pass a mixed gas of ammonia and nitrogen, wherein the mixed gas contains 4 volume % ammonia and the balance is nitrogen, heat to 750°C for 4 hours, cool to room temperature, take out, and then add to an aqueous solution containing 18wt% dopamine, then add tris(hydroxymethyl)aminomethane) of the same mass as dopamine, add hydrochloric acid to adjust the Ph value of the mixed solution to 7.5, heat to 70°C for 30 minutes, filter, wash, and dry to obtain modified carbon fiber;
[0045] 3) The composite fiber of step 1) and the modified carbon fiber of step 2) are put into deionized water at a mass ratio of 10:1 for dispersion, pulping, decomposition, papermaking, and hot pressing to obtain a PPS diaphragm; the pulping concentration is 4wt%, the papermaking concentration is 0.6%, the hot pressing pressure is 20Mpa, and the hot pressing temperature is 220°C;
[0046] 4) dispersing 22 parts by mass of polysulfone and 18 parts by mass of tris(2-hydroxyethyl)isocyanurate in 100 parts by mass of isopropanol to obtain an oily solution, dispersing 10 parts by mass of polyethyleneimine and 6 parts by mass of polyvinylpyrrolidone in 100 parts by mass of a mixed solvent of diethylene glycol and deionized water to obtain an aqueous solution, wherein the mass ratio of diethylene glycol to deionized water is 3:7;
[0047] 5) The PPS membrane obtained in step 3) is first immersed in an oily solution, kept for 8 minutes, taken out, dried, and then immersed in an aqueous solution, kept for 8 minutes, taken out, and dried. The above process is repeated 3 times to obtain the PPS membrane.
[0048] Comparative Example 1
[0049] 1) 90 parts by weight of polyphenylene sulfide and 28 parts by weight of polyether sulfone are mixed, heated to 310° C. for melt spinning, and cut to obtain PPS composite fibers; the number average molecular weight of the polyphenylene sulfide is 25,000; the number average molecular weight of the polyether sulfone is 45,000, and the number average molecular weight of the lignin is 1,200;
[0050] 2) The composite fiber of step 1) is put into deionized water for dispersion, pulping, decomposition, papermaking, and hot pressing to obtain a PPS separator; the pulping concentration is 4wt%, the papermaking concentration is 0.6%, the hot pressing pressure is 20Mpa, and the hot pressing temperature is 220°C;
[0051] 3) dispersing 22 parts by mass of polysulfone and 18 parts by mass of tris(2-hydroxyethyl)isocyanurate in 100 parts by mass of isopropanol to obtain an oily solution, dispersing 10 parts by mass of polyethyleneimine and 6 parts by mass of polyvinylpyrrolidone in 100 parts by mass of a mixed solvent of diethylene glycol and deionized water to obtain an aqueous solution, wherein the mass ratio of diethylene glycol to deionized water is 3:7;
[0052] 4) The PPS membrane was immersed in an oily solution, kept for 8 minutes, taken out, dried, and then immersed in an aqueous solution, kept for 8 minutes, taken out, and dried. The above process was repeated 3 times to obtain the PPS membrane.
[0053] Comparative Example 2
[0054] 1) 90 parts by weight of polyphenylene sulfide, 28 parts by weight of polyether sulfone, and 10 parts by weight of lignin are mixed, heated to 310° C. for melt spinning, and cut to obtain PPS composite fibers; the number average molecular weight of the polyphenylene sulfide is 25,000; the number average molecular weight of the polyether sulfone is 45,000, and the number average molecular weight of the lignin is 1,200;
[0055] 2) The composite fiber of step 1) is put into deionized water for dispersion, pulping, decomposition, papermaking, and hot pressing to obtain a PPS separator; the pulping concentration is 4wt%, the papermaking concentration is 0.6%, the hot pressing pressure is 20Mpa, and the hot pressing temperature is 220°C;
[0056] 3) dispersing 22 parts by mass of polysulfone and 18 parts by mass of tris(2-hydroxyethyl)isocyanurate in 100 parts by mass of isopropanol to obtain an oily solution, dispersing 10 parts by mass of polyethyleneimine and 6 parts by mass of polyvinylpyrrolidone in 100 parts by mass of a mixed solvent of diethylene glycol and deionized water to obtain an aqueous solution, wherein the mass ratio of diethylene glycol to deionized water is 3:7;
[0057] 4) The PPS membrane was immersed in an oily solution, kept for 8 minutes, taken out, dried, and then immersed in an aqueous solution, kept for 8 minutes, taken out, and dried. The above process was repeated 3 times to obtain the PPS membrane.
[0058] Comparative Example 3
[0059] 1) 90 parts by weight of polyphenylene sulfide, 28 parts by weight of polyether sulfone, and 10 parts by weight of lignin are mixed, heated to 310° C. for melt spinning, and cut to obtain PPS composite fibers; the number average molecular weight of the polyphenylene sulfide is 25,000; the number average molecular weight of the polyether sulfone is 45,000, and the number average molecular weight of the lignin is 1,200;
[0060] 2) adding carbon fiber to 1.0 mol / L hydrochloric acid, heating at 75° C. for 6 h, filtering, washing, and drying to obtain activated carbon fiber; adding the activated carbon fiber to an aqueous solution containing 18 wt % dopamine, then adding tris(hydroxymethyl)aminomethane) in an amount equal to that of dopamine, adding hydrochloric acid to adjust the pH value of the mixed solution to 7.5, heating to 70° C. for 30 min, filtering, washing, and drying to obtain modified carbon fiber;
[0061] 3) The composite fiber of step 1) and the modified carbon fiber of step 2) are put into deionized water for dispersion, beating, debonding, papermaking, and hot pressing to obtain a PPS diaphragm; the beating concentration is 4wt%, the papermaking concentration is 0.6%, the hot pressing pressure is 20Mpa, and the hot pressing temperature is 220°C;
[0062] 4) dispersing 22 parts by mass of polysulfone and 18 parts by mass of tris(2-hydroxyethyl)isocyanurate in 100 parts by mass of isopropanol to obtain an oily solution, dispersing 10 parts by mass of polyethyleneimine and 6 parts by mass of polyvinylpyrrolidone in 100 parts by mass of a mixed solvent of diethylene glycol and deionized water to obtain an aqueous solution, wherein the mass ratio of diethylene glycol to deionized water is 3:7;
[0063] 5) The PPS membrane obtained in step 3) is first immersed in an oily solution, kept for 8 minutes, taken out, dried, and then immersed in an aqueous solution, kept for 8 minutes, taken out, and dried. The above process is repeated 3 times to obtain the PPS membrane.
[0064] Comparative Example 4
[0065] 1) 90 parts by weight of polyphenylene sulfide, 28 parts by weight of polyether sulfone, and 10 parts by weight of lignin are mixed, heated to 310° C. for melt spinning, and cut to obtain PPS composite fibers; the number average molecular weight of the polyphenylene sulfide is 25,000; the number average molecular weight of the polyether sulfone is 45,000, and the number average molecular weight of the lignin is 1,200;
[0066] 2) adding carbon fiber to 1.0 mol / L hydrochloric acid, heating at 75° C. for 6 h, filtering, washing, and drying to obtain activated carbon fiber; adding the activated carbon fiber to n-butanol, adding zirconium n-butoxide, wherein the concentration of zirconium n-butoxide is 4 wt %, adding acetic acid to adjust the Ph value to 6.0, heating to 65° C., acidifying and hydrolyzing, filtering the product, washing,
[0067] After drying, the mixture is placed in a heating furnace and introduced with a mixture of ammonia and nitrogen, wherein the mixture contains 5% by volume of ammonia.
[0068] The balance is nitrogen, heated to 750°C and kept for 4 hours, cooled to room temperature, taken out, and modified carbon fiber was obtained;
[0069] 3) The composite fiber of step 1) and the modified carbon fiber of step 2) are put into deionized water for dispersion, beating, debonding, papermaking, and hot pressing to obtain a PPS diaphragm; the beating concentration is 4wt%, the papermaking concentration is 0.6%, the hot pressing pressure is 20Mpa, and the hot pressing temperature is 220°C;
[0070] 4) dispersing 22 parts by mass of polysulfone and 18 parts by mass of tris(2-hydroxyethyl)isocyanurate in 100 parts by mass of isopropanol to obtain an oily solution, dispersing 10 parts by mass of polyethyleneimine and 6 parts by mass of polyvinylpyrrolidone in 100 parts by mass of a mixed solvent of diethylene glycol and deionized water to obtain an aqueous solution, wherein the mass ratio of diethylene glycol to deionized water is 3:7;
[0071] 5) The PPS membrane obtained in step 3) is first immersed in an oily solution, kept for 8 minutes, taken out, dried, and then immersed in an aqueous solution, kept for 8 minutes, taken out, and dried. The above process is repeated 3 times to obtain the PPS membrane.
[0072] Comparative Example 5
[0073] 1) 90 parts by weight of polyphenylene sulfide, 28 parts by weight of polyether sulfone, and 10 parts by weight of lignin are mixed, heated to 310° C. for melt spinning, and cut to obtain PPS composite fibers; the number average molecular weight of the polyphenylene sulfide is 25,000; the number average molecular weight of the polyether sulfone is 45,000, and the number average molecular weight of the lignin is 1,200;
[0074] 2) adding carbon fiber to 1.0 mol / L hydrochloric acid, heating at 75° C. for 6 h, filtering, washing, and drying to obtain activated carbon fiber; adding the activated carbon fiber to n-butanol, adding zirconium n-butoxide, wherein the concentration of zirconium n-butoxide is 4 wt %, adding acetic acid to adjust the Ph value to 6.0, heating to 65° C., acidifying and hydrolyzing, filtering the product, washing,
[0075] After drying, the mixture is placed in a heating furnace and introduced with a mixture of ammonia and nitrogen, wherein the mixture contains 5% by volume of ammonia.
[0076] The balance is nitrogen, heated to 750°C for 4 hours, cooled to room temperature, taken out, and then added to an aqueous solution containing 18wt% dopamine, and then tris(hydroxymethylaminomethane) of the same mass as dopamine was added, and hydrochloric acid was added to adjust the Ph value of the mixed solution to 7.5, heated to 70°C for 30 minutes, filtered, washed, and dried to obtain modified carbon fibers;
[0077] 3) The composite fiber of step 1) and the modified carbon fiber of step 2) are put into deionized water for dispersion, pulping, decomposition, papermaking and hot pressing to obtain a PPS diaphragm; the pulping concentration is 4wt%, the papermaking concentration is 0.6%, the hot pressing pressure is 20Mpa, and the hot pressing temperature is 220°C.
[0078] Comparative Example 6
[0079] 1) 90 parts by weight of polyphenylene sulfide, 28 parts by weight of polyether sulfone, and 10 parts by weight of lignin are mixed, heated to 310° C. for melt spinning, and cut to obtain PPS composite fibers; the number average molecular weight of the polyphenylene sulfide is 25,000; the number average molecular weight of the polyether sulfone is 45,000, and the number average molecular weight of the lignin is 1,200;
[0080] 2) adding carbon fiber to 1.0 mol / L hydrochloric acid, heating at 75° C. for 6 h, filtering, washing, and drying to obtain activated carbon fiber; adding the activated carbon fiber to n-butanol, adding zirconium n-butoxide, wherein the concentration of zirconium n-butoxide is 4 wt %, adding acetic acid to adjust the Ph value to 6.0, heating to 65° C., acidifying and hydrolyzing, filtering the product, washing,
[0081] After drying, the mixture is placed in a heating furnace and introduced with a mixture of ammonia and nitrogen, wherein the mixture contains 5% by volume of ammonia.
[0082] The balance is nitrogen, heated to 750°C for 4 hours, cooled to room temperature, taken out, and then added to an aqueous solution containing 18wt% dopamine, and then tris(hydroxymethylaminomethane) of the same mass as dopamine was added, and hydrochloric acid was added to adjust the Ph value of the mixed solution to 7.5, heated to 70°C for 30 minutes, filtered, washed, and dried to obtain modified carbon fibers;
[0083] 3) The composite fiber of step 1) and the modified carbon fiber of step 2) are put into deionized water for dispersion, beating, debonding, papermaking, and hot pressing to obtain a PPS diaphragm; the beating concentration is 4wt%, the papermaking concentration is 0.6%, the hot pressing pressure is 20Mpa, and the hot pressing temperature is 220°C;
[0084] 4) dispersing 18 parts by mass of tris(2-hydroxyethyl)isocyanurate in 100 parts by mass of isopropanol to obtain an oily solution, dispersing 10 parts by mass of polyethyleneimine in 100 parts by mass of a mixed solvent of diethylene glycol and deionized water to obtain an aqueous solution, wherein the mass ratio of diethylene glycol to deionized water is 3:7;
[0085] 5) The PPS membrane obtained in step 3) is first immersed in an oily solution, kept for 8 minutes, taken out, dried, and then immersed in an aqueous solution, kept for 8 minutes, taken out, and dried. The above process is repeated 3 times to obtain the PPS membrane.
[0086] Comparative Example 7
[0087] 1) 90 parts by weight of polyphenylene sulfide, 28 parts by weight of polyether sulfone, and 10 parts by weight of lignin are mixed, heated to 310° C. for melt spinning, and cut to obtain PPS composite fibers; the number average molecular weight of the polyphenylene sulfide is 25,000; the number average molecular weight of the polyether sulfone is 45,000, and the number average molecular weight of the lignin is 1,200;
[0088] 2) adding carbon fiber to 1.0 mol / L hydrochloric acid, heating at 75°C for 6h, filtering, washing, and drying to obtain activated carbon fiber; adding the activated carbon fiber to n-butanol, adding zirconium n-butoxide, wherein the concentration of zirconium n-butoxide is 4wt%, adding acetic acid to adjust the Ph value to 6.0, heating to 65°C, acidifying and hydrolyzing, filtering, washing, and drying the product, and then placing it in a heating furnace in air and heating it to 750°C for 4h, cooling it to room temperature, taking it out, and then adding it to an aqueous solution containing 18wt% dopamine, and then adding tris(hydroxymethyl)aminomethane in an amount equal to that of dopamine, adding hydrochloric acid to adjust the Ph value of the mixed solution to 7.5, heating it to 70°C for 30min, filtering, washing, and drying it to obtain modified carbon fiber;
[0089] 3) The composite fiber of step 1) and the modified carbon fiber of step 2) are put into deionized water for dispersion, beating, debonding, papermaking, and hot pressing to obtain a PPS diaphragm; the beating concentration is 4wt%, the papermaking concentration is 0.6%, the hot pressing pressure is 20Mpa, and the hot pressing temperature is 220°C;
[0090] 4) dispersing 22 parts by mass of polysulfone and 18 parts by mass of tris(2-hydroxyethyl)isocyanurate in 100 parts by mass of isopropanol to obtain an oily solution, dispersing 10 parts by mass of polyethyleneimine and 6 parts by mass of polyvinylpyrrolidone in 100 parts by mass of a mixed solvent of diethylene glycol and deionized water to obtain an aqueous solution, wherein the mass ratio of diethylene glycol to deionized water is 3:7;
[0091] 5) The PPS membrane obtained in step 3) is first immersed in an oily solution, kept for 8 minutes, taken out, dried, and then immersed in an aqueous solution, kept for 8 minutes, taken out, and dried. The above process is repeated 3 times to obtain the PPS membrane.
[0092] Performance Testing
[0093] The average pore size of the separators of the embodiments of the present invention and the comparative examples is 5±0.1 μm, the porosity is 50±1%, and the thickness is 300±3 μm.
[0094] For breaking strength, refer to GB / T3923.1-2013.
[0095] Strength loss rate test method,
[0096] The diaphragm was placed in a 30 wt % KOH solution and heated to 80° C. for 300 h, and the breaking strength loss rate was calculated: strength loss rate = breaking strength difference before and after heat treatment / breaking strength before heat treatment.
[0097] The bubble point test refers to GB / T 32361-2015.
[0098] Table 1
[0099] Breaking strength(Mpa) Strength loss rate (%) Bubble point (mbar) Example 1 45.6 2.85 38.2 Example 2 46.8 2.95 37.6 Example 3 46.2 2.80 38.5 Comparative Example 1 28.5 6.20 32.6 Comparative Example 2 34.8 5.75 34.5 Comparative Example 3 42.5 3.20 36.8 Comparative Example 4 39.5 3.55 35.6 Comparative Example 5 38.0 4.05 33.5 Comparative Example 6 41.5 3.85 36.2 Comparative Example 7 44.8 3.05 37.4
[0100] Results Data
[0101] It can be seen from the data of the embodiments and comparative examples that the addition of lignin can improve the crystallization properties of polyethersulfone and polyphenylene sulfide, thereby improving the mechanical properties and corrosion resistance of the PPS composite fiber; the acidic hydrolysis coating of zirconate improves the mechanical properties of carbon fiber and improves the coating effect of polydopamine on carbon fiber; polydopamine and composite PPS fiber have excellent affinity and adhesion, thereby improving the bonding effect between carbon fiber and PPS fiber and improving the breaking strength of PPS diaphragm; polysulfone, tris (2-hydroxyethyl) isocyanurate, polyethyleneimine, and polyvinyl pyrrolidone can improve the breaking strength of the diaphragm; the atmosphere of the heat treatment of carbon fiber will also have a significant impact on the mechanical properties of the diaphragm.
[0102] Although the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as limiting the present invention.
Claims
1. A method for preparing a PPS diaphragm for increasing the fracture strength of the PPS diaphragm, characterized in that: include: 1) Mix polyphenylene sulfide, polyether sulfone, and lignin, heat to above 300°C for melt spinning, and cut to obtain PPS composite fiber; 2) adding carbon fiber to hydrochloric acid, heating, filtering, washing, and drying to obtain activated carbon fiber; adding the activated carbon fiber to n-butanol, adding zirconium n-butoxide, adding acetic acid to adjust the Ph value, heating for acidification and hydrolysis, filtering the product, washing, and drying, and then placing it in a heating furnace into which a mixed gas of ammonia and nitrogen is introduced, heating to 700-800° C. for insulation, cooling to room temperature, taking it out, and then adding it to an aqueous solution containing dopamine, and then adding trishydroxymethylaminomethane, adding hydrochloric acid to adjust the Ph value of the mixed solution, heating for in-situ polymerization and coating, filtering, washing, and drying to obtain modified carbon fiber; 3) putting the composite fiber of step 1) and the modified carbon fiber of step 2) into deionized water for dispersion, pulping, debonding, papermaking, and hot pressing to obtain a PPS separator; 4) dispersing polysulfone and tris(2-hydroxyethyl)isocyanurate in isopropanol to obtain an oily solution, and dispersing polyethyleneimine and polyvinylpyrrolidone in a mixed solvent of diethylene glycol and deionized water to obtain an aqueous solution; 5) The PPS membrane obtained in step 3) is first immersed in an oily solution, maintained, taken out, dried, and then immersed in an aqueous solution, maintained, taken out, and dried. The above process is repeated multiple times to obtain the PPS membrane.
2. The preparation method according to claim 1, characterized in that In step 1), 80-100 parts by mass of polyphenylene sulfide, 25-30 parts by mass of polyether sulfone, and 8-12 parts by mass of lignin are mixed, heated to 300-320° C. for melt spinning, and cut to obtain PPS composite fibers; the number average molecular weight of the polyphenylene sulfide is 20,000-30,000; the number average molecular weight of the polyether sulfone is 40,000-50,000, and the number average molecular weight of the lignin is 1,000-1,200.
3. A preparation method according to claim 1, characterized in that: In step 2), the carbon fiber is added to 0.8-1.2 mol / L hydrochloric acid, heated at 70-80°C for 4-8h, filtered, washed, and dried to obtain activated carbon fiber; the activated carbon fiber is added to n-butanol, zirconium n-butoxide is added, wherein the concentration of zirconium n-butoxide is 3-5wt%, acetic acid is added to adjust the Ph value to 5.5-6.5, heated to 60-70°C, acidified and hydrolyzed, the product is filtered, washed, dried, and then placed in a heating furnace and passed through A mixed gas of ammonia and nitrogen, wherein the mixed gas contains 2-5 volume % ammonia and the balance is nitrogen, is heated to 700-800°C and kept warm for 3-5 hours, cooled to room temperature, taken out, and then added to an aqueous solution containing 15-20wt% dopamine, and then tris(hydroxymethyl)aminomethane) of the same mass as dopamine is added, and hydrochloric acid is added to adjust the Ph value of the mixed solution to 7-8, heated to 60-80°C and kept for 20-40 minutes, filtered, washed, and dried to obtain modified carbon fibers.
4. The preparation method according to claim 1, characterized in that: In step 3), the mass ratio of the composite fiber to the modified carbon fiber is 10-15:1-2; the pulping concentration is 3-5wt%, the papermaking concentration is 0.5-0.8%, the hot pressing pressure is 15-20Mpa, and the hot pressing temperature is 200-240°C.
5. The preparation method according to claim 1, characterized in that: In step 4), 20-25 parts by mass of polysulfone and 15-20 parts by mass of tris(2-hydroxyethyl)isocyanurate are dispersed in 100 parts by mass of isopropanol to obtain an oily solution.
6. The preparation method according to claim 1, characterized in that: In step 4), 8-12 parts by mass of polyethyleneimine and 5-8 parts by mass of polyvinylpyrrolidone are dispersed in a mixed solvent of 100 parts by mass of diethylene glycol and deionized water to obtain an aqueous solution, wherein the mass ratio of diethylene glycol to deionized water is 3:7-2:
8.
7. The preparation method according to claim 1, characterized in that: In step 5), the PPS membrane obtained in step 3) is first immersed in an oily solution, kept for 5-10 minutes, taken out, dried, and then immersed in an aqueous solution, kept for 5-10 minutes, taken out, dried, and the above process is repeated 2-5 times to obtain the PPS membrane.
8. A PPS diaphragm with high breaking strength, characterized in that: The diaphragm is prepared by the preparation method according to any one of claims 1 to 7.
